STRUKTUR SEMANTIS VERBA “MENCIPTAKAN” BAHASA ARAB: KAJIAN METABAHASA SEMANTIK ALAMI - Effendi, Sultan Salman; Harahap, Annisah Inriani; Mulyadi, Mulyadi (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This study aims to explain the meaning of the verb "create" to a single word with a single meaning or otherwise using the MSA theory. The data used in this study consists of Arabic words, phrases, and sentences that contain the significance of the verba "Create". The method used for gathering data is the slide and talk method. The analysis of this research data includes qualitative descriptive using agih methods and variable techniques, expansion techniques, injection techniques, and parafrase techniques. In this study, there are data showing five lexicons meaning “create” with different entities to express the verb: verba أبدع /abda’a/, ابتكر /ibtakara/, خلق /khalaqa/, اخترع /ikhtara’a/ and أوجد /awjada/. Verba أبدع / Abda’a/- or ابتدع /ibtada’a./ is a “creating” verb used to describe the transitional word “creates” for something new or renews the previous creation and is also meant as creation with creativity like an idea. And Verba اخترع/ikhtara’a/- is the “creation” verb indicating the creation or discovery of something new. Then the verba ابتكر/ibtakara/- is a verba “created” which produces a creation in the presence of a structured design. Then verba خلق/qaqa/ is a verb meaning something created (no one has ever created before) with the measure of the will or the rule of the original creation verba that has never been created.